Associations between traditional Chinese medicine constitution and depression/anxiety/sleep disturbances in patients with chronic pain: A cross-sectional study - Shiqi Guo; Cunzhi Liu; Liqiong Wang; Jianfeng Tu; Tie Li; Yong Fu; Zhongyu Zhou; Changchun Ji; Hui Hu; Nana Yang (Journal of Traditional Chinese Medical Sciences)
Objective: To investigate the relationship between the composition of traditional Chinese medicine (TCM) and depression/anxiety/sleep disturbances (D/A/S) in patients with chronic pain. Methods: This cross-sectional study was conducted at 13 tertiary hospitals across China, enrolling patients who experienced chronic pain between November 2023 and May 2024. The Patient Health Questionnaire-9, Generalized Anxiety Disorder-7, Pittsburgh Sleep Quality Index, and TCM constitution categories were used to assess the patients. The association between the TCM constitution and the D/A/S ratio was analyzed using multivariable logistic regression. Results: A total of 1107 patients (63.2% women) were analyzed. Compared with those with a balanced constitution, patients who had qi-deficiency and yin-deficiency were at a higher risk of depression. Qi-deficiency and yin-deficiency were associated with anxiety. Sleep disturbances were common in patients with qi-deficiency constitution (odds ratio [OR]: 2.32, 95% confidence interval [CI]: 1.42–3.81), yang-deficiency constitution (OR: 1.94, 95% CI: 1.26–2.98), yin-deficiency constitution (OR: 2.03, 95% CI: 1.24–3.32), blood stasis constitution (OR: 2.07, 95% CI: 1.01–4.22), and qi-stagnation constitution (OR: 2.66, 95% CI: 1.35–5.25). Conclusion: In patients with chronic pain, specific TCM constitutions may be associated with D/A/S. Further longitudinal studies are needed to clarify the potential causal relationships between TCM constitution types and these conditions.